Trauma and beyond : the mystery of transformation - Wirtz, Ursula, 1946- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"In this seminal work on the clinical, archetypal and spiritual dimension of trauma, the author offers a compelling vision of the transformative potential of suffering and the dialectic of Dying and Becoming. Wirtz outlines a healing path from fragmentation to integration and illuminates the resilience of the human spirit in the face of severe trauma. Trauma and Beyond will be essential reading and a valuable resource for counsellors, therapists and Jungian analysts who are challenged in their practice with individual and collective traumata"--
"First published 2014 by Spring Journal Books."
OCLC-licensed vendor bibliographic record.
Keywords: Psychic trauma; Ego (Psychology); Soul; Psychotherapy; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian